2003
DOI: 10.1111/j.1151-2916.2003.tb03313.x
|View full text |Cite
|
Sign up to set email alerts
|

Powder‐Based Tin Oxide Microcomponents on Silicon Substrates Fabricated by Micromolding in Capillaries

Abstract: With the introduction of soft lithography and micromolding in capillaries, low‐cost microfabrication with liquid materials has become possible. In this article, we demonstrate how to fabricate porous ceramic lines of 10 μm width and several millimeter length on silicon wafer substrates by using colloidal suspensions of tin oxide. Microchannels of poly(dimethylsiloxane) (PDMS) served as molds that were spontaneously filled owing to capillary forces with suspensions of 0.1–40 vol% solid loading. The resulting ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…The filling rate also decreased because of the continuous drying of dispersions during the MIMIC process. These observations agree with the results of Heule et al [19], although those authors used molds with semi-circular channels.…”
Section: Dispersion-derived T I O 2 Patternssupporting
confidence: 83%
See 1 more Smart Citation
“…The filling rate also decreased because of the continuous drying of dispersions during the MIMIC process. These observations agree with the results of Heule et al [19], although those authors used molds with semi-circular channels.…”
Section: Dispersion-derived T I O 2 Patternssupporting
confidence: 83%
“…As a result, the penetration length was shorter for narrow than wide channels. Heule et al [19] reported on the patterning of powder-based tin oxide (SnO 2 ) patterns by MIMIC. The formation of fork-shaped spikes was attributed to the faster penetration of the solution in the corners of the channels.…”
Section: Patterning Of T I O 2 With Micromolding In Capillariesmentioning
confidence: 99%
“…The other class of starting liquids studied are colloidal suspensions of ceramic powders, as reported by Gauckler et al 1) who demonstrated that low-cost ceramic microstructures are easily generated using suspensions of high solid loading (e.g., more than 15 vol%). However, with colloidal suspensions, the infiltration lengths of the suspension into the capillaries is short because the suspensions are non-Newtonian fluids and therefore are continuously drying while infiltration is taking place.…”
Section: Introductionmentioning
confidence: 99%
“…From there, the slurry enters the capillaries on all four sides of the pattern. Compared to stamp designs with an open suspension reservoir, 13) this stamp design avoids drying of the suspension in the reservoir prior to the drying of the suspension in the channels.…”
Section: Slurry Preparation and Film Depositionmentioning
confidence: 99%
“…Thicknesses of several micrometers can then be achieved. 13), 14) MIMIC of ceramic suspensions has been optimized by several groups. As complete channel infiltration is impeded by high values of suspension viscosity, Imasu et al 15) used low solid content slurries to reduce the viscosity and successfully obtained millimeter long stripes.…”
Section: Introductionmentioning
confidence: 99%